PENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATIS MELALUI PEMBELAJARAN DENGAN STRATEGI THINK TALK WRITE (TTW) DI SEKOLAH DASAR - Siti Quratul Ain; Eva Astuti Mulyani (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2018)
This study aims to examine improving students' mathematical understanding through Think Talk Write learning strategy. The method is a quasi-experiment with experimental class research design and the pretest-posttest control class. The experimental class implemented the Think Talk Write learning strategy and the control class by direct learning model. The population of this study is a fourth-grader of one elementary school in Bandung. The sample in this research is 50 students, two classes. The instrument used in data collection is a test of the mathematical understanding ability of the description form. The result data were N-gain score analyzed by using independent-test t-test and Mann-Whitney test. From this research, I obtained the conclusion, improving students’ mathematical understanding ability who get learning with Think Talk Write strategy is better than students who gain learning by direct learning.